Giant cell myocarditis causing sudden death in a patient with sarcoidosis - John P. Ziegler; Nicholas I. Batalis; James W. Fulcher; Michael E. Ward (University of São Paulo, 2021)
Giant cell myocarditis (GCM) is a rare and rapidly fatal cardiovascular condition most often seen in young adults. It is characterized microscopically by myocardial necrosis with multinucleated giant cells in the absence of well-defined granulomas. This disorder has typically been attributed to manifest as heart failure, but in some individuals, GCM may present as sudden cardiac death. Herein, we present a fatal case of GCM in a 36-year-old male with a history of autoimmune disorders. The decedent presented to the emergency room due to vomiting and was treated for nausea due to suspected dehydration. He was discharged that night and found dead on his bathroom floor the following day. Postmortem examination revealed psoriasis and granulomatous lesions in the lungs consistent with sarcoidosis, further supporting circumstantial evidence existing between GCM and autoimmune disorders. Additionally, this case provides an opportunity to distinguish GCM from the distinct clinical entity of cardiac sarcoidosis (CS), especially in the setting of systemic sarcoidosis. We hope to raise awareness of this rare disease process and its potential to cause sudden cardiac death so that it may be considered in a differential diagnosis as immunosuppression and early cardiac transplantation largely determine the prognosis.